Taking the middle road to market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Market facilities Taking the middle road to market How markets perform depends a lot on their facilities. ACP countries have strengthened their efforts in the last decade, but most market facilities are inadequate, or non-existent - particularly in...